2009
DOI: 10.1212/wnl.0b013e3181c3fd2a
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal recessive Bethlem myopathy

Abstract: The reported patients illustrate the occurrence of Bethlem myopathy with a recessive mode of inheritance. This observation completes the hereditary pattern in collagen VI myopathies with both Ullrich congenital muscular dystrophy and Bethlem myopathy underlined by either recessive or dominant effecting mutations. This finding has relevant implications for genetic counseling and molecular characterization of patients with Bethlem myopathy, as well as for genotype-phenotype correlations in collagen VI disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 28 publications
1
44
0
Order By: Relevance
“…These data emphasize the critical importance of the ␣2(VI) C2 domain in monomer and microfibril assembly. Further, electron microscopy of the collagen VI fibrils deposited by the patient with compound heterozygous mutations, ␣2(VI) p.Q819X and p.D871N, in which only ␣2(VI) C2a chains are likely to be incorporated into secreted collagen VI molecules, revealed that the microfibrils in the extracellular matrix did not develop the extensive interconnections seen control microfibrils (4). This finding suggests that the ␣2(VI) C2a domain is also important in promoting interactions between collagen VI microfibrils and raises the possibility that inclusion of this domain in collagen VI tetramers might modulate collagen VI microfibril formation and interactions with other extracellular matrix molecules.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These data emphasize the critical importance of the ␣2(VI) C2 domain in monomer and microfibril assembly. Further, electron microscopy of the collagen VI fibrils deposited by the patient with compound heterozygous mutations, ␣2(VI) p.Q819X and p.D871N, in which only ␣2(VI) C2a chains are likely to be incorporated into secreted collagen VI molecules, revealed that the microfibrils in the extracellular matrix did not develop the extensive interconnections seen control microfibrils (4). This finding suggests that the ␣2(VI) C2a domain is also important in promoting interactions between collagen VI microfibrils and raises the possibility that inclusion of this domain in collagen VI tetramers might modulate collagen VI microfibril formation and interactions with other extracellular matrix molecules.…”
Section: Discussionmentioning
confidence: 97%
“…A molecular diagnosis of recessive Bethlem myopathy has been reported in only three families (4,6). A family with myosclerosis myopathy, a disorder with considerable clinical overlap with Bethlem myopathy, also has recessive collagen VI mutations (5).…”
mentioning
confidence: 99%
“…Genomic DNA was extracted from lymphocytes by standard methods. In the elder proband (II1, Fig.1) all three COL6 genes were sequenced as previously described 3 . Younger girl and parents were sequenced only for exons 10 and 29.…”
Section: Methods/ Molecular Studiesmentioning
confidence: 99%
“…It is well known that ColVI is abundantly expressed by skin fibroblasts, and indeed, human skin biopsies and in vitro primary skin fibroblast cultures have been widely used to characterize ColVI defects in Bethlem myopathy and UCMD individuals (Lamandé et al, 1999(Lamandé et al, , 2002Sasaki et al, 2000;Zhang et al, 2002;Gualandi et al, 2009;Martoni et al, 2009). Not surprisingly, several skin abnormalities, such as keloids or 'cigarette paper' scars, dry skin, striae rubrae and follicular keratosis, have been described in individuals with mutations in the COL6A1, COL6A2 or COL6A3 genes Lettmann et al, 2014).…”
Section: Skinmentioning
confidence: 99%